Nematodes of the genus Dirofilaria Railliet et Henry, 1911, parasites of carnivorous mammals in Uzbekistan: spread and ecology - A. A. Safarov; F. J. Akramova; J. A. Azimov (Российский паразитологический журнал, 2022)
The purpose of the research is study of some issues of fauna, spread and ecology of nematodes of the genus Dirofilaria in biogeocenoses of Uzbekistan.Materials and methods. Nematodes of the genus Dirofilaria (D. immitis and D. repens) were collected from domestic and wild carnivorous mammals within Uzbekistan. The studies were carried out during 2015–2021. 559 individuals of carnivorous mammals were studied by the method of complete helminthological dissection. The found parasites were collected and fixed according to generally accepted methods. The helminths and ectoparasites were identified and their morphology was studied by temporary and permanent specimens using modern microscopes. The parasite species was identified in accordance with the keys and descriptions given in the papers by domestic and foreign researchers. To identify intermediate hosts of Dirofilaria (D. immitis), mosquitoes (Culicidae) were caught and examined on and around dogs. A total of 4064 specimens of mosquitoes were studies in spring, summer and autumn using the generally accepted method. We determined the prevalence and intensity of helminth infection in carnivorous. To study the nucleotide sequences in Dirofilaria, we used mature nematodes D. immitis and D. repens collected from dissected animals. Live nematodes were washed in saline (0.9% NaCl) and fixed in 70% ethanol. We conducted the isolation of genomic DNA, PCR amplification, electrophoresis and sample analysis.Results and discussion. In total, two species of Dirofilaria were found in representatives of carnivores in Uzbekistan, namely, D. immitis (Leidy, 1856) and D. repens Railliet et Henry, 1911. Original data on the spread of Dirofilaria in domestic and wild carnivores, as well as some materials on D. immitis intermediate hosts recorded from mosquitoes Aedes caspius and Culex pipiens were presented. The mtDNA-COI nucleotide sequences were determined to identify species of mature nematodes D. immitis (MN 650648.1), and D. repens (MZ 081850.1) was deposited by GenBank.